PENGARUH TERAPI NON FARMAKOLOGI DALAM MENGURANGI KECEMASAN PADA IBU HAMIL DI ERA PANDEMI COVID 19 : LITERATUR REVIEW - Fibrinika Tuta Setiani; Dewi Candra Resmi (Jurnal Ilmiah Kesehatan, 2020)
Objective: To determine the effect of non-pharmacological therapy in reducing anxiety inpregnant women in the era of COVID-19 pandemic. Method: The method used in this Literature review is to search for publication resultsbetween 2019-2020 through MIDLINE, ProQuest, Google Scoolar, and PubMed searches. The search results obtained using the Boolean method in the form of full text and pdf, thenreviewed using the CASP (Critical Appraisal Skill Program), extracted then discussed andconcluded. Results: The results of literature reviews from four related journals that met the criteria of theresearchers showed that social support, Murottal Al-Qur'an therapy, yoga for pregnantwomen and motivational interviewing had an effect on reducing anxiety in pregnant women. Conclusion: Non-pharmacological therapy in the management of anxiety for pregnantcy inthe era of COVID-19 pandemic can be carried out with social support, Murottal Al-Qurantherapy, yoga for pregnant women and motivational interviewing